Found, and wandering lost - Kissell, Kevin, author; Lundberg, Thomas R., advisor; Coronel, Patricia D., committee member; Littrell, Mary, committee member; Faris, Suzanne, committee member (Colorado State University. Libraries, 2008)
To view the abstract, please see the full text of the document.
Keywords: Textile fabrics